An interval chance-constrained fuzzy modeling approach for supporting land-use planning and eco-environment planning at a watershed level. (15th December 2017) - Ou, Guoliang; Tan, Shukui; Zhou, Min; Lu, Shasha; Tao, Yinghui; Zhang, Zuo; Zhang, Lu; Yan, Danping; Guan, Xingliang; Wu, Gang
Abstract: An interval chance-constrained fuzzy land-use allocation (ICCF-LUA) model is proposed in this study to support solving land resource management problem associated with various environmental and ecological constraints at a watershed level. The ICCF-LUA model is based on the ICCF (interval chance-constrained fuzzy) model which is coupled with interval mathematical model, chance-constrained programming model and fuzzy linear programming model and can be used to deal with uncertainties expressed as intervals, probabilities and fuzzy sets. Therefore, the ICCF-LUA model can reflect the tradeoff between decision makers and land stakeholders, the tradeoff between the economical benefits and eco-environmental demands. The ICCF-LUA model has been applied to the land-use allocation of Wujiang watershed, Guizhou Province, China. The results indicate that under highly land suitable conditions, optimized area of cultivated land, forest land, grass land, construction land, water land, unused land and landfill in Wujiang watershed will be [5015, 5648] hm 2, [7841, 7965] hm 2, [1980, 2056] hm 2, [914, 1423] hm 2, [70, 90] hm 2, [50, 70] hm 2 and [3.2, 4.3] hm 2, the corresponding system economic benefit will be between 6831 and 7219 billion yuan. Consequently, the ICCF-LUA model can effectively support optimized land-use allocation problem in various complicated conditions which include uncertainties, risks, economic objective and eco-environmental constraints. Graphical abstract: Highlights: An interval chance-constrained fuzzy land-use allocation model is proposed. The problem is modeled under environmental, ecological, social conditions. The model can reflect tradeoff between decision makers and land stakeholders. The results can help make the utmost of land resources of Wujiang watershed.